2011
DOI: 10.1136/thoraxjnl-2011-200760
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor β and histone deacetylase 1 and 2 expression in the airways of severe asthma

Abstract: Rationale Upregulation of glucocorticoid receptor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 36 publications
2
47
0
1
Order By: Relevance
“…GR-α is ubiquitously expressed and is responsible for the induction and Nanzer et al 16 repression of target genes, while GR-ß is expressed at much lower levels and is a dominant negative inhibitor of GR-α. Increased expression of GR-ß has been linked with severe asthma in some studies (42,46), and a recent study suggested that IL-17A and IL-17F increase the expression of GR-ß, an effect that was more prominent in asthmatics than in healthy controls (23). These data imply a complex and potentially detrimental relationship between IL-17A, steroid treatment and responsiveness in severe asthma, on which vitamin D may have a positive impact.…”
Section: Nanzer Et Al 15mentioning
confidence: 89%
“…GR-α is ubiquitously expressed and is responsible for the induction and Nanzer et al 16 repression of target genes, while GR-ß is expressed at much lower levels and is a dominant negative inhibitor of GR-α. Increased expression of GR-ß has been linked with severe asthma in some studies (42,46), and a recent study suggested that IL-17A and IL-17F increase the expression of GR-ß, an effect that was more prominent in asthmatics than in healthy controls (23). These data imply a complex and potentially detrimental relationship between IL-17A, steroid treatment and responsiveness in severe asthma, on which vitamin D may have a positive impact.…”
Section: Nanzer Et Al 15mentioning
confidence: 89%
“…HDACs are critical proteins that repress the production of proinflammatory cytokines (9,11), and HDAC2 has been reported to be required for corticosteroid-mediated anti-inflammatory activity (18). HDAC2 expression and activity is regulated through PI3K-␦/Akt and, specifically, a decrease in PAkt levels may increase the expression of HDAC2 (25).…”
Section: Discussionmentioning
confidence: 99%
“…[10,21,22] Healthy controls (n=17), mild/moderate asthmatics (n=29) and severe asthmatics (n=18) were recruited from two UK specialist asthma centres, Belfast City Hospital and Glenfield Hospital, Leicester (demographic characteristics shown in Table 1). …”
Section: Patient Cohortmentioning
confidence: 99%